The photophysicochemical properties and photodynamic therapy activity of phenyldiazenyl phenoxy substituted phthalocyanines when incorporated into Pluronic® F127 micelles. (1st December 2019) - Mike Motloung, Banele; Edward Sekhosana, Kutloano; Managa, Muthumuni; Prinsloo, Earl; Nyokong, Tebello
Graphical abstract: 4(4-Phenyldiazenyl) phenoxy substituted indium(III) and zinc(II) phthalocyanines were incorporated into Pluronic® F127 micelles and the former showed higher singlet oxygen quantum yield and photodynamic therapy activity. Abstract: The synthesis, photophysicochemical properties and photodynamic activity (PDT) of 4(4-phenyldiazenyl) phenoxy substituted indium (III) (InPc) and zinc (ZnPc) phthalocyanines when alone or incorporated into Pluronic® F127 micelles are presented in this study. The InPc exhibited higher singlet oxygen (ΦΔ ) at 0.47 compared to the ZnPc at 0.20 in dimethylsulfoxide. The ΦΔ values in the presence of Pluronic® F127 and in water, were 0.32 for InPc and 0.09 for ZnPc. The triplet quantum yields (Φ T ) were 0.92 for InPc and 0.32 for ZnPc in DMSO. The PDT activity followed the same trend as the singlet oxygen quantum yields. At the highest concentration, InPc in Pluronic® F127 gave 22% cell viability compared to 34% for complex ZnPc. The partition coefficient K p values were determined using the water and octanol system. InPc had a larger K p suggesting that it is more likely to be taken up by the cancer cells, hence it exhibited better PDT activity.